Disclosure of Environment, Social, and Governance (ESG) implementation at PT Sinergi Gula Nusantara - Putri, Nabila Amelia; Ketut Bayangkara, I. B. (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The research conducted aims to reveal the implementation of the Environment, Social, and Governance (ESG) principles at PT Sinergi Gula Nusantara (SGN) in supporting business sustainability. The research method used is a qualitative approach with a literature study, which examines various secondary sources such as financial reports, articles, and journals. The results of the study show that SGN has implemented ESG comprehensively, including energy efficiency, biomass utilization, water and waste management, and emission reduction for environmental aspects; implementation of CSR programs, non-discrimination principles, employee training, and community welfare for social aspects; and the application of the principles of transparency, accountability, and good governance in governance aspects. SGN also received the ASRRAT 2024 award with a Bronze rating, which indicates the effectiveness of ESG implementation. These findings confirm that transparent ESG disclosure and implementation not only strengthen the company's sustainability but also increase competitiveness and contribution to national sustainable development.